Peranan PCO dalam Bidding Konferensi Asosiasi: 2021 Asia Pacific Cities Summit - Miranda Putri; Christina L. Rudatin (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
The party that is supposed to bid is the local association party. However, the bidding initiative can come from the PCO. PT Rajawali Pacific Internusa is a PCO that has the initiative to do